Knowledge, Perceptions and Practices about Oral Rehydration Therapy in Under Five Children Suffering from Diarrhea in Mirpur, AJK - Ijaz Ali, Hina Shafi, Jamil Ahmad, Sundus Shafi, Muhammad Usman Anjum, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Dehydration associated with diarrheal diseases is a leading cause of mortality. Most of these deaths can be prevented by preventing or timely treating dehydration and using oral rehydration therapy is one of the options. Aim: To evaluate the knowledge and practices associated with the preparation and use of oral rehydration therapy in pediatric patients suffering from diarrhea. Study design: Descriptive cross-sectional study, Place & duration of study: Mohi-ud-Din Teaching Hospital, Mirpur, AJK, from January to August 2021, Methods: Mothers and care-givers of children were selected. A structured questionnaire was used to assess the knowledge and practices of the participants. The information gathered included epidemiological and socio-demographic data as well as about the knowledge, attitude and practices regarding prevention of diarrhea, usage, preparation and mode of administration of oral rehydration therapy among study respondents. Result: Mean age of care givers was 31.53±5.973 years. Mean income of a household was 28233±10986 PKR while median income was 30000 PKR. As per the employment status, 78.33% were housewives and 21.67% of women were working. Regarding the educational status, 15.67% were illiterate while 84.33% were literate. About 46.66% of the participants knew about the various ways to prevent diarrhea. Regarding the knowledge and assessment of practices of care givers about home-based remedies and ORT, majority of the participants, 78.33%, knew about ORT, 75% have used ORT and 69.33% knew about how to prepare ORT. Furthermore, 64.66% prepared ORT using standard method and 65% knew that ORT replaced lost water in the body. Conclusion: There was a high level of information and awareness among caregivers about the oral rehydration therapy, its correct preparation, usage and method of administration leading to its appropriate usage in diarrhea patients. But still there is a need to increase the awareness among people by mass awareness campaigns to better inform the masses and to maximize the acceptability, usage and benefits of oral rehydration therapy. Keywords: Dehydration, diarrhea, rehydration, therapy, oral